Enhancing 3D scene understanding via text annotations - Partsey, Ruslan; Teslyuk, Vasyl; Maksymets, Oleksandr; Humennyy, Vladyslav; Kuzma, Volodymyr (Eastern-European Journal of Enterprise Technologies, 2025)
The object of this study is the use of text annotations as a form of 3D scene representation. The paper investigates the task of integrating large-scale language models (LLMs) into complex 3D environments. Using the Embodied Question Answering task as an example, we analyze different types of scene annotations and evaluate the performance of LLMs on a subset of test episodes from the OpenEQA dataset. The aim of the study was to evaluate the effectiveness of textual scene descriptions compared to visual data for solving EQA tasks. The methodology implied estimating the optimal context length for scene annotations, measuring the differences between free-form and structured annotations, as well as analyzing the impact of model size on performance, and comparing model results with the level of human comprehension of scene annotations. The results showed that detailed descriptions that include a list of objects, clearly described attributes, spatial relationships, and potential interactions improve EQA performance, even outperforming the most advanced method in OpenEQA – GPT-4V (57.6 % and 58.5 % for GPT-4 and LLaMA-2, respectively, vs. 55.3 % for GPT-4V). The results can be explained by the high level of detail that provides the model with contextually clear and interpretable information about the scene. The optimal context length for textual descriptions was estimated to be 1517 tokens. Nevertheless, even the best textual representations do not reach the level of perception and reasoning demonstrated by humans when presented with visual data (50 % for textual data vs. 86.8 % for video). The results are important for the development of multimodal models for Embodied AI tasks, including Robotics and Autonomous Navigation Systems. They could also be used to improve user interaction with three-dimensional spaces in the field of virtual or augmented reality